2018
DOI: 10.3233/jad-171180
|View full text |Cite
|
Sign up to set email alerts
|

From Subjective Cognitive Decline to Alzheimer’s Disease: The Predictive Role of Neuropsychological Assessment, Personality Traits, and Cognitive Reserve. A 7-Year Follow-Up Study

Abstract: The aim of this study was to evaluate the accuracy of neuropsychological assessment in predicting conversion from subjective cognitive decline (SCD) and mild cognitive impairment (MCI) to Alzheimer's disease (AD) and the effect of personality traits and cognitive reserve in progression from SCD to MCI. As part of a longitudinal, clinical-neuropsychological-genetic survey on SCD and MCI, 284 patients referred to our hospital between 1990 and 2017 were included. All patients underwent clinical-extensive neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 88 publications
5
67
1
7
Order By: Relevance
“…Only a few longitudinal studies of people with carefully phenotyped SCD have investigated the rate of progression of SCD to dementia due to AD [ 13 , 14 ]. With clinical advances, the increasing number of memory clinics will facilitate the enrollment of subjects with SCD and increase awareness about SCD and the concept of cognitive protection.…”
Section: Standard Terminology and Diagnostic Criteriamentioning
confidence: 99%
“…Only a few longitudinal studies of people with carefully phenotyped SCD have investigated the rate of progression of SCD to dementia due to AD [ 13 , 14 ]. With clinical advances, the increasing number of memory clinics will facilitate the enrollment of subjects with SCD and increase awareness about SCD and the concept of cognitive protection.…”
Section: Standard Terminology and Diagnostic Criteriamentioning
confidence: 99%
“…The advent of genetics and imaging has taken some emphasis away from the critical need to focus on developing better detailed methods to understand normal cognition, cognitive decline and the myriad of other issues occurring alongside AD and dementia more broadly. There are clearly limitations to cognitive testing regimens for dementia [ 102 , 104 , 206 ], indicating more sophisticated neuropsychological assessments are required to better predict and define cognitive and other changes [ 21 , 102 , 217 ], particularly in preclinical stages of disease [ 182 ]. This would likely have a profound impact on predictive power [ 199 ].…”
Section: If Not Centred On Aβ How Could Disease Prediction and Diagnmentioning
confidence: 99%
“…Mild cognitive impairment (MCI) is an intermediate condition between normal cognition and dementia and is associated with an increased risk of dementia 6 . Previous studies have indicated that high education, 7 and social, cognitive, or intellectual activity 8‐10 might be related to decreased incidence of MCI among cognitively intact individuals. So far, no studies have examined the association of lifespan CR indicator with the risk of MCI.…”
Section: Introductionmentioning
confidence: 99%